Optical Coherence Tomography Doppler Vibrometry Measurement of Stapes Vibration in Patients With Stapes Fixation and Normal Controls. Issue 4 (April 2019) - MacDougall, Dan; Morrison, Loran; Morrison, Christine; Morris, David P.; Bance, Manohar; Adamson, Robert B. A.
Abstract : Hypothesis: Ears with otosclerotic stapes fixation will exhibit lower-than-normal levels of ossicular mobility as measured by Optical Coherence Tomography Doppler Vibrometry (OCT-DV). Background: OCT-DV measures the vibration of middle ear structures in response to sound non-invasively through the intact tympanic membrane. This allows, in particular, direct measurement of the vibration at the lenticular process of the incus which is expected to be lower in patients with otosclerotic stapes fixation. Methods: OCT-DV was performed on ears presumptively diagnosed with otosclerosis (n = 13) and a group of normal control ears (n = 42). Displacement was measured at the umbo and the lenticular process of the incus in response to 500 and 1000 Hz stimulus tones at 100 dBSPL . Main Outcome Measure: The ability to discriminate between groups was assessed using receiver operator characteristic analysis, with the main outcome measures being the area-under-curve (AUC) and the sensitivity and specificity. Results: For the best condition tested (500 Hz at the incus), the AUC was 0.998 and discriminated the otosclerotic from normal ears with a sensitivity/specificity of 1.00/0.98. One anomalous patient with surgically confirmed stapes fixation exhibited hypermobility at the umbo, possibly due to a partial ossicular discontinuity. Despite the high umbo mobility, this patient's stapes fixation was correctly discriminated based on the measured incus vibration levels. Conclusions: OCT-DV is a promising tool for preoperatively assessing ossicular mobility non-invasively in the clinic. Our results suggest OCT-DV may also be useful in discriminating other ossicular pathologies that result in conductive hearing loss.